2010
DOI: 10.1210/en.2010-0566
|View full text |Cite
|
Sign up to set email alerts
|

Increased PTHrP and Decreased Estrogens Alter Bone Turnover but Do Not Reproduce the Full Effects of Lactation on the Skeleton

Abstract: During lactation, calcium is mobilized from the maternal skeleton to supply the breast for milk production. This results in rapid but fully reversible bone loss. Prior studies have suggested that PTHrP, secreted from the breast, and estrogen deficiency, due to suckling-induced central hypogonadism, combine to trigger bone resorption. To determine whether this combination was sufficient to explain bone loss during lactation, we raised PTHrP levels and decreased levels of estrogens in nulliparous mice. PTHrP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…We have previously observed that infusion of PTHrP (1–36) into virgin mice for 11 days caused a modest degree of bone loss both at the spine (5.2±1.2%) and at the femur (4.5±1.8%) (13) . BSEM showed osteocyte lacunar area was significantly increased in vertebral trabecular bone (34.1±2.3*, μm 2 ) from PTHrP-treated mice as compared to placebo-treated mice (30.7±1.9) *p<0.05 (n=5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously observed that infusion of PTHrP (1–36) into virgin mice for 11 days caused a modest degree of bone loss both at the spine (5.2±1.2%) and at the femur (4.5±1.8%) (13) . BSEM showed osteocyte lacunar area was significantly increased in vertebral trabecular bone (34.1±2.3*, μm 2 ) from PTHrP-treated mice as compared to placebo-treated mice (30.7±1.9) *p<0.05 (n=5).…”
Section: Resultsmentioning
confidence: 99%
“…PTHrP-treated mice received a continuous infusion of PTHrP (1–36) subcutaneously using Alzet mini-osmotic pumps (model 2002) at a rate of 10pmol/hr until sacrifice on day 12, as described in our previous publications (13) .…”
Section: Methodsmentioning
confidence: 99%
“…bone volume, trabecular thickness). The threshold was set at 375 mg HA/cm 3 to distinguish mature bone from the residual scaffold and soft tissue [37]. …”
Section: Methodsmentioning
confidence: 99%
“…This process of rapid bone loss is associated with increased bone turnover and increased numbers of surface osteoclasts and bone resorption. Furthermore, this process is triggered in part by the secretion of PTHrP from the breast 535455. PTHrP interacts with the same type 1 PTH/PTHrP receptor (PTHR1) in bone as does PTH.…”
Section: Reversible Osteocytic Perilacunar and Canalicular Remodelingmentioning
confidence: 99%